Adaptive E-learning Environment To Improve Creative Thinking Learning Process - Hanan Etaher Dagez, Hassan Al Sari (Journal of Pure & Applied Sciences, 2019)
E-learning plays an important role in the spread of knowledge because of the great development in information technology and the spread of the Internet. Recent years have seen the attention of information technology smart systems in the development of the concept of e-learning and despite the efficiency of computer-based training systems CBT and Computer Assisted Instruction CAI in helping learners, However, they do not offer individual attention to the student as in face to face learning system. This paper present adaptive e-learning system to support creative thinking learner.